PENGARUH PELATIHAN PLAIOMETRIK DOUBLE LEG BOUND TERHADAP PENINGKATAN POWER OTOT TUNGKAI - Kharisma, N. Riang (Universitas Pendidikan Ganesha, 2013)
The research aimed to determine the effect of training plaiometrick double leg bound to increase leg muscle power. This research is a quasi experimental research (quasi-experimental) with the design of the Modified Control Group Pretest Posttest Design. The study population was a student of class VII student son football extracurricular participants SMP N 3 Singaraja school year 2012/2013, amounting to 96 people. The subjects of the training plaiometrick double leg bound numbered 96 people. Limb muscle power was measured with a standing broad jump test, then the data were analyzed by independent t-test at significance level (α) of 0.05 with SPSS 16.0. Based on the results of independent t-test results obtained for variable leg muscle power, the results of the treatment group and the gaint score control group obtained the value thitung = 11.391 with a significance value of 0.000. Calculated significance value smaller than the value of α (Sig <0.05), thus the research hypothesis